2014
DOI: 10.1021/ac502296c
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Amino Acid Epimerization and Isomerization in Crystallin Proteins by Tandem LC-MS

Abstract: Post-translational modifications that do not result in a change in mass are particularly difficult to detect by mass spectrometry. For example, isomerization of aspartic acid or epimerization of any chiral residue within a peptide do not lead to mass shifts but can be identified by examination of independently acquired tandem mass spectra or by combination with another technique. For analysis of a biological sample, this means that liquid chromatography or some other type of separation must be used to first se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
101
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(102 citation statements)
references
References 45 publications
1
101
0
Order By: Relevance
“…It seems that an H 2 PO 4 − ion has an effective proton relay ability. It has recently been elucidated that the majority of Ser (and Asp) residues that are susceptible to racemization reside in flexible regions of proteins [26][27][28]. If a Ser residue can adopt such a conformation as shown in Figure 2 and then its α-proton and carbonyl oxygen are exposed to solvent water, it is likely to undergo enolization (and hence racemization) by the mechanism revealed in the present study.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…It seems that an H 2 PO 4 − ion has an effective proton relay ability. It has recently been elucidated that the majority of Ser (and Asp) residues that are susceptible to racemization reside in flexible regions of proteins [26][27][28]. If a Ser residue can adopt such a conformation as shown in Figure 2 and then its α-proton and carbonyl oxygen are exposed to solvent water, it is likely to undergo enolization (and hence racemization) by the mechanism revealed in the present study.…”
Section: Discussionmentioning
confidence: 52%
“…Indeed, we did not find a corresponding stable conformation for the main chain of the analogous alanine (Ala)-containing compound (Ace-Ala-Nme); instead, a conformer with ϕ = 73 • and ψ = −56 • was located because of the formation of an intramolecular hydrogen bond between the oxygen of Ace and the hydrogen of Nme (1.932 Å). It has been experimentally observed that Ser residue racemization occurs mainly in flexible regions of proteins [26][27][28]. Therefore, the existence of the above reactive conformer unique to Ser may be one of the reasons why Ser residues are prone to racemization.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, many outstanding methods for the analysis of peptide-containing isomers [25,26] and epimers [27][28][29][30][31] using MS2 spectra have been reported. Although these methods are excellent, however, they require advanced instruments and expertise for analysis.…”
Section: Lc-ms/ms Using the Corresponding Synthetic Peptides As Standmentioning
confidence: 99%
“…4,6,9−13,15−18 As a result, it is not surprising that many recent publications on amygdalin analysis do not mention/identify the S-amygdalin, which is always present to some extent depending on the storage conditions, extraction solvents, and analytical procedures. Although in a few specific cases, using advanced instrumentation such as MS-MS that may allow differentiation of epimers, 19,20 ideally it is desired and usually necessary that the epimers are separated chromatographically. Thus, the separation of the natural and its unwanted isomerized amygdalin is best done chromatographically.…”
Section: Journal Of Agricultural and Food Chemistrymentioning
confidence: 99%